() () = - . .

() = 4 + 33 - 52 + 2 - 5 () = - 1 () () (1).

(1):

() () -4.

:

 

 

 

 

 

 

 

 

 

 

      1 (1) = -4

() () .

() = 3 - 30 () = - 3 () ().

(2):

() 3 (3) = -3 () () () () -3.

:

1 2 () () = - 1 (1) () ()= - 3 (3).

:

() () = - ().

).

-

() () = + (

() () = -   () = () () () = () . () () .

() = 3 - 6 4() = + 2. () () .

(3):

() = + 2 (-2) =

:

(-2) = (-2)3 - 6 (-2) -4 = - 8 + 12 - 4 = .

 

(-2) = () () = .

 

() = ( + 2) () () .

 

 

() = 4 - 16 () = 2 - 4 () ().

(4):

(2) = (2) = 42 - 16 = 16 - 16 =

:

() () .

 

() = 4 - 16 = () (2 - 4) () .

 

3 4 () () :

 

 

() = - () () = 0 () = 0 - ().

) = 0

-

() = + () (

.

 

 

 

 

* () () :

() = - 1

1) () = 23 - 5 + 3

() = 2 - 4

2) () = 4 + 23 - 72 - 8 + 20

() = 2 + 3

3) () = 3 - 2 + 7

* () () :

() = + 2

4) () = 4 + 23 - 72 - 8 + 12

() = + 1

5) () = 5 + 1

() = 2 - 1

 

7

6) () = 23 - 4 +

 

4

() = 2 + 4

7) () = 4 - 32 + 5 + 6

 

 

 

 

 

* 8 11 () ().

() = 2 - 3

8) () = 25 - 43 - 64

() = 2 + 2

9) () = 4 - 16

 

1

() = +

10) () = 34 - 2 + 1

2

 

1

() = -

11) () = 23 + 32 - 4 - 5

2

 

* 12 15 () ().

() = - 2

12) () = 4 + 23 - 72 - 8 +12

() = 2 + 4

13) () = 4 - 16

() = - 2

14) () = 25 - 64

() = 2 - 1

15) () = 44 - 32 + 5 - 2

16) ( + 3) ( + 1) ( - 1) .

17)   - 2

() = 3 - 32 + - 1

18) () = ( + 3) 2 + 5 + 1 () = + 2 6.